Analysis of Irony in the Lyrics Arabic Song "A’touna Et-Tufoole" Study: Cognitive Semantics - Nurainun Hasibuan; Mulyadi Mulyadi (Randwick International of Education and Linguistics Science Journal, 2023)
This research examines Irony focusing on the lyrics of the song "A’touna Et-Tufoole" in Arabic version. The main objective of this research is to explore the meaning of irony in the lyrics of "A’touna Et-Tufoole" and analyze how the meaning of irony is employed within the context of the song. A qualitative approach with descriptive analysis method is employed to comprehend the meaning of irony and its descriptive qualitative implications. The research design involves content analysis of data consisting of Irony embedded in the lyrics of "A’touna Et-Tufoole" in Arabic. Data collection techniques employed in this research include reading and note-taking. The research findings encompass Verbal Irony, Dramatic Irony, and Situational Irony. This study aims to provide deeper insights into how irony functions in elucidating the meaning of songs in the Arabic language within the field of Arabic language semantics and how it might influence the understanding and interpretation of messages within different cultural contexts. Furthermore, this research is anticipated to make a significant contribution to comprehending the complex aspects of Arabic language irony.